Total Daily Physical Activity and the Risk of Parkinsonism in Community-Dwelling Older Adults. (2nd May 2019) - Oveisgharan, Shahram; Yu, Lei; Dawe, Robert J; Bennett, David A; Buchman, Aron S
Abstract: Background: Physical activity is a modifiable risk factor associated with health benefits. We hypothesized that a more active lifestyle in older adults is associated with a reduced risk of incident parkinsonism and a slower rate of its progression. Methods: Total daily physical activity was recorded with an activity monitor in 889 community-dwelling older adults participating in the Rush Memory and Aging Project. Four parkinsonian signs were assessed with a modified motor portion of the Unified Parkinson's Disease Rating Scale and summarized as a categorical measure and continuous global parkinsonian score. We used Cox models to determine whether physical activity was associated with incident parkinsonism and linear mixed-effects models to examine if physical activity was associated with the rate of progressive parkinsonism. Results: During an average follow-up of 4 years, 233 of 682 (34%) participants, without parkinsonism, developed incident parkinsonism. In Cox models controlling for age, sex, and education, a higher level of physical activity was associated with a reduced risk of developing parkinsonism (hazard ratio = 0.79; 95% CI = 0.70–0.88, p < .001). This association was not attenuated when controlling for cognition, depressive symptoms, Apolipoprotein E ℇ4 allele, and chronic health conditions. In a linear mixed-effects model including all participants ( N = 889) which controlled for age, sex, and education, a 1 SD total daily physical activity was associated with a 20% slower rate of progression of parkinsonism. Conclusion: Older adults with a more active lifestyle have a reduced risk for parkinsonism and a slower rate of its progression.